Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Cafe Tempat Ngupi Cinere - Rizkoh, Alfido; Nofiar Nofiar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study is to determine the effect of price and service quality on consumer satisfaction at Café Tempat Ngupi Cinere. The data analysis used is descriptive quantitative. The sampling technique used is probability sampling. The random sampling method uses the taroyamane formula with the acquisition of 98 respondents. Data analysis uses validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, T test and F test. The results show that: (1) partially there is a positive influence between price on consumer satisfaction at Café Tempat Ngupi Cinere, this can be proven from the multiple linear regression equation Y = 5.219 + 0.469 X1 and the calculated t value of 7.165 t table 1.665 with a sig. level of 0.00. (2) Partially there is a positive influence between service quality on customer satisfaction at the Cinere Ngupi Place Cafe, this can be proven from the multiple linear regression equation Y = 12.415 + 0.344 X2 and the calculated t value of 6.435 t table 1.665 with a sig. level of 0.01. (3) simultaneously there is a positive influence between price and service quality on customer satisfaction at the Cinere Ngupi Place Cafe, this can be proven from the multiple linear regression equation Y = 5.219 + 0.469X1 + 0.344X2, the correlation coefficient value is 0.643, the determination coefficient value is 41% while the remaining 59% is influenced by other factors, and the calculated f test is 33.411> f table 3.09 with a significance level of 0.000 <0.05. Thus H0 is rejected H3 is accepted. This means there is a significant influence between price and service quality on customer satisfaction at Café Tempat Ngupi Cinere.